The Evaluation and Promotion System-SISAP as a proposal for innovation in the promotion of the Federal Police - Nascimento, Sarah Brito do; Kern, Vinícius Medina (Advanced Notes in Information Science, 2023)
Innovation is essential for the survival of private organizations, but it is also relevant for public ones. In the Federal Police, the incorporation of digital innovations contributes to the achievement of institutional objectives. In this research, we investigate the evaluation and promotion process in the Brazilian Federal Police, in transition from predominantly manual to digitized execution, to describe the innovative characteristic of this digitalization process. This is bibliographic and documentary research with participatory observation. The research stages are: analyzing documents from the Evaluation and Promotion Service (SAP) - which are not systematized in software, observing and describing the evaluation and promotion process in digitization to be implemented in the Evaluation and Promotion System (SISAP), and studying the internal regulations of the Federal Police regarding its Innovation Policy and its implementation. The results include synthesizing innovation concepts in the public sector, with the specificity of the Federal Police's Innovation Policy materialized in developed actions. They also include analyzing the proposal for the Evaluation and Promotion System (SISAP) software as a possible innovation. In conclusion, SISAP is a proposal for administrative, incremental, and technological process innovation, in line with the culture of innovation in the public service and with the Federal Police's Innovation Policy, as well as its Strategic Plan.